2016
DOI: 10.3390/nu8010012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Theory-Based Education Program to Prevent Overweightness in Primary School Children

Abstract: The effectiveness of the “Extra Fit!” (EF!) education program in promoting healthy diet and physical activity to prevent and reduce overweightness among primary school children aged 9 to 11 was evaluated. A randomized controlled design was carried out in 45 primary schools (n = 1112) in the Netherlands, 23 intervention and 22 control schools. The intervention schools received the education program for two successive school years in grades (U.S. system) 4, 5, and 6 (mean 7.6 h during 16 weeks per school per yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 33 publications
(52 reference statements)
0
26
0
14
Order By: Relevance
“…Table 2 shows the descriptive characteristics and assessment of all three types of setting-based interventions, with Table 3 providing a summary of key characteristics of these setting-based interventions. Out of the total number of studies, seven were whole of community interventions [ 37 , 39 , 42 , 44 , 45 , 52 , 56 ], three were worksite-based interventions [ 34 , 36 , 43 ], and 23 were school-based interventions [ 24 33 , 35 , 38 , 40 , 41 , 46 51 , 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows the descriptive characteristics and assessment of all three types of setting-based interventions, with Table 3 providing a summary of key characteristics of these setting-based interventions. Out of the total number of studies, seven were whole of community interventions [ 37 , 39 , 42 , 44 , 45 , 52 , 56 ], three were worksite-based interventions [ 34 , 36 , 43 ], and 23 were school-based interventions [ 24 33 , 35 , 38 , 40 , 41 , 46 51 , 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the school-based interventions were cluster randomised [ 26 , 30 , 35 , 38 , 41 , 46 , 47 , 49 , 53 ] and one used historical controls [ 29 ]. All other 13 studies were quasiexperimental [ 24 , 25 , 27 , 28 , 31 33 , 40 , 48 , 50 , 51 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies [33][34][35][36][37][38][39][40][41] were investigated the simultaneous impact of education, nutrition and physical activity interventions on weight loss and dietary modification and lifestyle. The results of the studies indicated that the probability of success of these interventions is greater if the multidisciplinary method is used.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the development of technology in western societies is contributing to a growing sedentary lifestyle associated with various illnesses that are not only linked to the adult population (diabetes, high blood pressure, sleep disorders or arthritis, among others), but are also now present in the child and adolescent populations (Chacón, Zurita, Castro, Espejo, Martínez‐Martínez & Linares, 2016; Galíndez & Carmona, 2016). In this regard, awareness of the benefits that physical activity and sport can provide at the physical, psychological, and social level (American College of Sports Medicine, 2000), research‐based knowledge indicates that an active lifestyle should be adopted before reaching adolescence, since this stage is considered a critical period associated with individuals’ adherence and commitment to doing physical activity and sport (Kocken, Scholten, Westhoff, De Kok, Taal & Goldbohm, 2016; Wood & Hall, 2015).…”
mentioning
confidence: 99%